Value Added Tax and Economic Growth: An Empirical Study of China Perspective - Zeraibi Ayoub; Subhadeep Mukherjee (Signifikan: Jurnal Ilmu Ekonomi, 2019)
This study investigates the role of Value-Added Tax (VAT) on the economic growth in China. The data used for the study is a time series of the period from 1985-2016. These researches use the gross domestic product (GDP) as a dependent variable. For the independent variables, this research using the total population, employed persons, consumer price index, and value-added tax. The current findings add to a growing body of literature on identifying the properties of VAT in China and identifying the tax system reform from 1993 to 2012 and the mechanism of transfer application of the business tax in the services sector to Value-Added Tax. The test result indicated to have a positive relationship between the GDP and independent variables value-added tax in both in the long and short-run